Cowpea Mosaic Virus Promotes Anti‐Tumor Activity and Immune Memory in a Mouse Ovarian Tumor Model. Issue 5 (25th February 2019) - Wang, Chao; Fiering, Steven N.; Steinmetz, Nicole F.
Abstract: Cowpea mosaic virus (CPMV) is a promising platform nanotechnology with applications as a cancer therapeutic. To understand the therapeutic potential of CPMV in more detail, its antitumor mechanisms are investigated using a syngeneic immunocompetent murine orthotopic ovarian cancer model (ID8‐Defb29/Vegf‐A). CPMV treatment in situ promotes tumor regression and prevents tumor recurrence. Although CPMV does not kill tumor cells directly, it promotes an intra‐tumoral cytokine response which induces pre‐existing myeloid cells to break immunotolerance and initiate antitumor responses. The upregulation of interleukin‐6 and interferon‐γ as well as the downregulation of IL‐10 and transforming growth factor β are observed, associated with activation and repolarization of tumor‐associated macrophages and neutrophils to an anti‐tumor phenotype. Furthermore, the in situ administration of CPMV recruits dendritic cells and natural killer cells to the tumor site, and induces the expression of costimulatory molecules on CD11b – myeloid cells. By converting immunosuppressive myeloid cells into potent antigen‐presenting cells, in situ CPMV treatment significantly improves effector and memory CD4 + and CD8 + T cell responses and promoted systemic tumor‐specific cytotoxic CD8 + T cell activity. CPMV in situ immunotherapy induces significant tumor control in an aggressive ovarian tumor model by coordinating innate and adaptive immune responses involving neutrophils, macrophages, and T cells. Abstract : Cowpea mosaic virus (CPMV) in situ vaccination repolarizes immunosuppressive cells to immunostimulatory phenotypes and activates multiple potent antigen presenting cells (APCs). Naive tumor infiltrated T cells can then engage with receptors on those potent APCs presenting tumor antigens. These tumor‐specific T cells can activate tumor cell cytotoxicity and further expand to effector memory T cells.